A cyclopenta-fused dibenzo[b, d]thiophene-co-phenanthrene macrocyclic tetraradicaloid. Issue 11 (2nd February 2021) - Lu, Xuefeng; An, Dongyue; Han, Yi; Zou, Ya; Qiao, Yanjun; Zhang, Ning; Chang, Dongdong; Wu, Jishan; Liu, Yunqi
Abstract : The first member of sulfur-heterocycloarene neutral tetraradicaloids, MC4-S, was synthesized in crystalline form, which displays strong global anti-aromaticity and unique properties. Abstract : A cyclopenta-fused macrocyclic tetraradicaloid, MC4-S, containing alternating phenanthrene (Phen) and dibenzo[ b, d ]thiophene (DBTh) units was synthesized and isolated in single-crystal form. Compared with its all-carbon isoelectronic structure, CPTP-M, the incorporation of two sulfur atoms leads to a smaller radical character and a larger singlet–triplet energy gap. X-ray crystallographic analysis reveals that the spin–spin coupling through the DBTh unit is stronger than that through the Phen moiety. In addition, the electron-rich sulfur atoms also raise the energies of both the HOMO and LUMO in MC4-S, but the overall optical and electronic energy gaps are close to that of the CPTP-M . MC4-S displays global anti-aromaticity according to the NMR measurements and theoretical calculations (NICS, ACID and 2D ICSS), with a 36π ring current circuit along the all-carbon periphery excluding the two sulphur atoms. Its dication becomes globally aromatic due to the existence of a dominant 34π-conjugation pathway. This study sheds some light on the effect of heteroatoms on the electronic properties of open-shell polyradicaloids.